Gender on translation evaluation in Malaysia - S., Vijayaletchumy (2011)
This research investigate the relationship between the gender of a translator and the gender of the evaluator of the work of that translator. The researcher hypothesizes that if a rater is ti evaluate a translated text done by both a man and a woman, he sould unconsciously choose the translation of the same gender and vice versa. 20 men and 20 women senior students of the translation training program at Institut Terjemahan Negara were selected and participated in the experiment. The test included 20 questions; it was designed based on two translation of one chapter of a short story which was translated one by a male and the other by a female translator from English to Malay language. Two of the answer options were the translations of the two translators and the others were wrong translations. The subjects were asked to choose just the one which was nearest to their own opinions. Finally, the data analysis of the study showed that the relationship between the variables of the study was not proved and the research hyphothesizes was rejected. The limitations and implications of this study, as well as its suggestions for future research, are also discussed.